The System of Factors Determining the Prevention and Counteraction of Corruption in Estonia - Khoma, Nataliia; Vdovychyn, Ihor (PRAWO i WIĘŹ, 2024)
The aim of the paper is to develop a system of factors that have influenced anti-corruption processes in Estonia. The factors that have contributed to the progress and the factors that hinder Estonia from achieving zero corruption are identified. Special aspects of anti-corruption reforms in Estonia at the institutional level are identified. The methodological basis of the research is neo-institutionalism and axiological analysis; they allowed to construct a system of factors of two types: (1) those that contributed/contribute to the anti-corruption progress of Estonia (2) those that hamper Estonia’s advance towards zero corruption.